Minat Belajar Mahasiswa IAIN Surakarta Saat Pembelajaran Daring Ketika Pandemi - Amelia Fitri Rahmawati; Arisa Wafa Az Zahra; Kama Ratih (Literasi : Jurnal Kajian Keislaman Multi-Perspektif, 2021)
The world is still hit by the Covid-19 pandemic which has changed all lines of life. Education has also been affected by Covid-19, namely the implementation of online learning policies. This research is intended to express students' interest in learning in participating in online lectures during the pandemic. This study uses a qualitative method with a phenomenological approach, the results show that interest in learning online is influenced by internal and external factors. Internal factors come from emotional, student enthusiasm in learning, and ability to understand the material. While external factors are influenced by supporting infrastructure, the way lecturers deliver material, and the circumstances around students when they are online. Based on the results of the interviews, the researchers found findings in the form of ways for each student to increase interest in learning when online. Interest in learning will have an influence on student learning outcomes. Therefore, it is important to know the factors that make students excited to learn even though they are online.